2008
DOI: 10.1021/la7025973
|View full text |Cite
|
Sign up to set email alerts
|

Species and Density of Implant Surface Chemistry Affect the Extent of Foreign Body Reactions

Abstract: Implant-associated fibrotic capsule formation presents a major challenge for the development of long term drug release microspheres and implantable sensors. Since material properties have been shown to affect in vitro cellular responses and also to influence short term in vivo tissue responses, we have thus assumed that the type and density of surface chemical groups would affect the degree of tissue responses to microsphere implants. To test this hypothesis, polypropylene particles with different surface dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 88 publications
(264 reference statements)
3
44
0
Order By: Relevance
“…This was observed in both macrophage mono-cultures and cocultures, illustrated by their accumulated distance, while macrophages on CH 3 and NH 2 SAMs had intermediate accumulated distances. It was reported elsewhere that OH-functionalized surfaces triggered a higher recruitment of CD11b+ cells and cell infiltration in animal implantation assays [71]. This could be related to the strong complement activation by OH groups via the alternative pathway activation [58] and could explain the higher motility of macrophages in the present study due to the presence of serum.…”
Section: Macrophage Migration Studiessupporting
confidence: 62%
“…This was observed in both macrophage mono-cultures and cocultures, illustrated by their accumulated distance, while macrophages on CH 3 and NH 2 SAMs had intermediate accumulated distances. It was reported elsewhere that OH-functionalized surfaces triggered a higher recruitment of CD11b+ cells and cell infiltration in animal implantation assays [71]. This could be related to the strong complement activation by OH groups via the alternative pathway activation [58] and could explain the higher motility of macrophages in the present study due to the presence of serum.…”
Section: Macrophage Migration Studiessupporting
confidence: 62%
“…However, the results from experiment day 56 of the present study indicate that the host response improves in the long term. Using a similar experimental design to that of Kamath et al (s.c. implantation of surface-modified polypropylene microspheres in mice), Nair et al recently demonstrated that variations in the surface density of OH and COOH groups deposited by plasma treatment had only a relatively minor influence on the extent of the foreign body reaction [22]. As outlined above, the experimental model in the present study is different from that used by Nair et al in a number of relevant aspects.…”
Section: Discussionmentioning
confidence: 59%
“…Since it is well established that positive charged nanoparticles have high affinity to negative charged cell membrane protein [48], it is likely that JHU cell membranes were saturated with -NH 2 functionalized particles at lowest concentration (0.1 mg/ml) employed. In addition, using polypropylene microparticles [49], we find that the density of surface functionality has little influence on cell:particle interactions. Therefore, the increase in the surface NH 2 concentration, or the increased exposure to NH 2 groups in the case of nanoparticles, may not have a significant effect on cell survival.…”
Section: Discussionmentioning
confidence: 85%
“…Perhaps, the positive charged amine group prompts a destructive impact on the negatively charged membrane of the cells. The absence of a further decrease in cell viability may be explained by results from a recent study which shows that the properties of a surface functional group override the effects of increases in density or concentration of the functionality [49]. While the positive charged -NH 2 coating shows a significantly lower viability for JHU cells compared to uncoated TiO 2 , negatively charged -COOH coated particles have substantially higher cell viability levels except at potential overload concentrations.…”
Section: Discussionmentioning
confidence: 97%